Bio-sourced, low density cellulose-based fiber composites for sporting goods - Tee, Ru Ting Jessica (2016)
Ocean levels and the temperature of sea beds have been observed to be progressively increasing with time. In a bid to save natural resources and produce less environmental waste, industries like the automotive industry and sports have put together research teams to venture into “green” alternatives for their products. Natural fiber composites (a.k.a biocomposites) made with flax fibers are becoming popular as flax fibers have shown to be the next alternative to conventional fibers like glass. Flax fibers have specific stiffness similar to glass fibers. However, flax composites typically have inferior performance when subjected to impact especially when combined with a thermoset resin such as epoxy. This hinders their application to sporting goods. This study seeks to ultimately contribute to the understanding and improvement to the impact behaviour of flax composites to widen their use in sporting goods. Flax laminates were first manufactured using a hot press. Panels were manufactured from two types of fabrics, woven and unidirectional flax fibers with a thermoplastic matrix (polypropylene). Different composite layups were explored: 0̊/90̊ (cross-ply), 45̊/-45̊ (quadri-isotropic) and 0̊ (unidirectional) to understand the effects of layup. The flexural properties of the flax composite were then measured and compared to a benchmark panel made of epoxy. Panels were then subjected to falling weight impact tests at energies at 4.67J and 7.3J for unidirectional fibers and, 15J and 19J for woven fibers which will result in strength reduction of equal or greater than 40%. The damage was evaluated visually and flexural after impact tests were performed to measure the residual strength. Results from this study indicated that the flax fiber/polypropylene composite had similar specific stiffness to glass fibers currently used in sporting goods. They also indicated that the difference in damage tolerance between the studied layups was not significant. Future studies should investigate the use of fibers chemical treatments to improve the damage tolerance of this class of composites.